The Impact of Discovery Learning Models on The Critical Thinking Ability of Students at Middle-School - Hidayatul, Ainiyah; Nasution, Nasution; Nugroho, Purnomo Hari (International Journal for Educational and Vocational Studies, 2020)
This study intends to describe the effect of the Discovery Learning model on students' critical thinking skills in the 8th grade of junior high school. This type of research is quantitative with the method used is Quasi-Experiment. The subject of this research is 8-th grade Middle-School 2 Candi Sidoarjo consisting of an experimental grade and a control grade. Based on the results of data analysis and discussion shows that the activities of teachers in social studies learning meet the criteria both in the experimental group and better than the control class, student activity in improving students' critical thinking skills in the experimental group is better than the control class, student responses meet the positive categories, and there is a significant and influence/difference at a significant level of 5% (0.05) with a significant value or p-value of 0,000, so it can be concluded that the Discovery Learning learning model has a significant on students' critical thinking skills on material in the country's geographical conditions ASEAN countries through the atlas compared to conventional models. Characterized by the results of students 'critical thinking tests, 80.75% of students obtained an N-gain of 0.7 and the teacher's activities were carried out well and students' activities were actively and more enthusiastic in learning social studies.